Knapp's 'State Theory of Money' and its reception in German academic discourse - Dirk H. Ehnts (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
In 1905, Georg Friedrich Knapp published The State Theory of Money in his native German, claiming that money is a "creature of law" and not connected to metals via some intrinsic value. When the English translation appeared in 1924, apparently at the wishes of John Maynard Keynes, the German version had run through four editions, upon which the last the translation builds. There also had been considerable debate about "Chartalism" - the idea that money derived its acceptance by legal means - in the German academic literature. Among others, Knut Wicksell and Georg Simmel commented on it. Since so far there has not been any English-language publication on this issue, it is deemed worthwhile to provide such. After presenting the main arguments that Knapp makes in his book, the academic reviews that followed are presented and evaluated.
Keywords: E40; E42; E51; F31; H20; 330; chartalism; Modern Monetary Theory; monetary theory; public finance; deficit spending; taxation; value of money; metallism